COMPARATIVE EFFICACY OF COMBINED LOW-INTENSITY EXTRACORPOREAL SHOCKWAVE THERAPY AND ORAL THERAPY VS ORAL THERAPY ALONE FOR CHRONIC PELVIC PAIN SYNDROME: A META-ANALYSIS OF RANDOMIZED CONTROLLED TRIAL - Nurakbariansyah, Rocky; Soebadi, Doddy M.; Djatisoesanto, Wahjoe; Renaldo, Johan (Indonesian Journal of Urology, 2021)
Objective: This study aimed to compare the efficacy of Low-Intensity Extracorporeal Shockwave Therapy (Li-ESWT) and oral therapy combination compared to sole oral therapy for reducing symptoms in CP/CPPS patients. Material & Methods: A systematic search was conducted from the electronic database including PubMed, Clinicaltrial.gov, and Cochrane Library, published up to July 2020 following the PRISMA guideline. We screened RCTs with the inclusion criteria and assessed the quality with the Cochrane Risk of Bias tool. The primary outcome was the National Institute of Health Chronic Prostatitis Symptom Index (NIH-CPSI) and subgroup analysis for triple therapy users was conducted to improve interpretability. The analysis was performed using Review Manager 5.3. Results: A total of 2 RCTs consisted of 91 CP/CPPS patients were analyzed. Pooled analysis showed that compared to the oral therapy only group, combination therapy had a significant lower NIH-CPSI total score at the endpoint of the treatment (MD -7.46, 95% CI -9.85 to -5.07, p<0.001) and NIH-CPSI component pain score (MD -3.48, 95% CI -5.04 to -1.93, p<0.0001), urinary symptoms score (MD -0.96, 95% CI -1.47 to -0.45, p<0.001), and quality of life (QoL) impact score (MD -2.94; 95% CI -3.68 to -2.20, p=<0.001). Conclusion: This review revealed that patients undergoing combination Li-ESWT therapy have lower total NIH-CPSI scores than patients receiving oral therapy alone, this finding is consistent with each component of the score: pain, urinary symptoms, and impact on QoL.